BUILDING BRIDGES WITH THE TARGETED COMMUNITIES THROUGH DIFFERENT ACTIVITIES IN MUSEUMS (Scientific journal of the Fergana State University, 2023)
To identify a wide range of museum activities and their roles with regard to implementation of cultural heritage among people through establishing these activities in museums. Two methods are used to gather information on specific research area. The first method  is interview with museum curators and marketers, the second one is questionnaire survey with visitors. Main suggestions can be obtained from the research; a wide variety of museum activities are discussed in this article,  museum curators can use these implementation tools to improve the social status of museums among people. Museum activities should be more engaging and innovative in digital era to attract  a  large number of visitors. The majority of museums are currently  adopting to unexpected changes and innovative ideas of the  modern world.